Heresy - Bowden, Oliver (Assassin's creed, 2016)
The new book set in the universe of Assassin's Creed. Reliving the memories of his ancestor who fought beside Joan of Arc, high-ranking Templar Simon Hathaway slowly uncovers secrets of the past that could dangerously impact his present ... and that of the entire Templar order. An endless conflict. An old wrong. A new revelation. Simon Hathaway, member of the Templar Inner Sanctum, brings a cool head and detached manner to his new role as Head of Abstergo Industry's Historical Research Division. But Simon also has an insatiable curiosity, and is fascinated by the thought of experiencing history first-hand through his ancestor Gabriel Laxart, who fought alongside the legendary Joan of Arc. When he enters the newly-designed Animus for its initial project, Simon finds himself unprepared for what he discovers: how deep the conflict between the Templars and the Assassins goes, and what his ancestor is willing to do for the woman he loves. And as he slowly uncovers secrets of the past, Simon is confronted with the most dangerous truth of all: Who is the heretic ... and who is the true believer?